(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The Aerobic Gymnastics is a complex sport and the movements are performed continuously, intensely at high speed with the musical accompaniment. One can directly assess the overall performance to the naked eye, but is not able to assess the individual elements of movement and technical aspects. The video analysis indirectly, through the ability to stop and review the various stages of movement several times, facilitates the evaluation. The aim of this study is to verify whether the use of video analysis in daily training activities can facilitate the evaluations of the coaches. 4 female athletes will be evaluated using the tabs in the Code of Points with annotations for deductions (0.10 slight error, mean error 0:20, 0:50 fault) and after 30 sessions in two different ways. The athletes are divided into two groups: 1) Control which continues to be evaluated with the traditional forms, 2) Experimental which is evaluated through the use of two cameras, which apply the points of repelle on specific anatomical points. At the end all the athletes will be traditionally evaluated and one will compare the assessments to highlight the difference between the two groups. The athletes in the experimental group improved at 0.30 and 0.40 compared to initial assessments made without the video analysis and compared to the control group. The experimental group compared with the control group has a better final evaluations in the matter of execution and cleanliness of the gesture. Probably the rapidity of correction of the act requested by the coach after watching the video and the subsequent execution of the athlete support proper execution. This new training methodology may be also tested on athletes, in order to allow a self-assessment through the measurement of the movie and the subsequent correction of performance so that it can better understand the errors committed and implicitly suggest the correction. The simultaneous use of video analysis by athletes and coaches during the training could further improve the result.